2001
DOI: 10.1590/s0100-204x2001000500005
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization impact on agronomic traits of maize hybrids released at different decades

Abstract: Genetic selection of maize hybrids is often conducted using high N rates during the breeding cycle. This procedure may either lead to the release of genotypes that present nitrogen luxury consumption or require a stronger N input to accomplish their yield potential. This work was carried out to evaluate the effects of N rates on grain yield and N use efficiency of hybrids cultivated in different decades in Southern Brazil. The trial was performed in Lages, Santa Catarina State. A split plot design was used. Hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 21 publications
(24 reference statements)
3
20
0
10
Order By: Relevance
“…(2009) reported that the amount of N taken up varied with hybrids and was higher in high responsive hybrids. Sangoi et al (2001) similarly reported that older hybrids took up more N and presented higher values of shoot dry matter at flowering. Kamoni et al (2000) had also found that N is taken up by maize throughout the growing season with maximum uptake 10 days before tasselling to 25 to 30 days after tasselling.…”
Section: Mineral N At the Different Stages Of Maize Growthmentioning
confidence: 80%
“…(2009) reported that the amount of N taken up varied with hybrids and was higher in high responsive hybrids. Sangoi et al (2001) similarly reported that older hybrids took up more N and presented higher values of shoot dry matter at flowering. Kamoni et al (2000) had also found that N is taken up by maize throughout the growing season with maximum uptake 10 days before tasselling to 25 to 30 days after tasselling.…”
Section: Mineral N At the Different Stages Of Maize Growthmentioning
confidence: 80%
“…The crop takes up between 20 and 25 kg of soil N per ton of grain (Muzilli & Oliveira, 1992;Sangoi et al, 2001a). Nitrogen is the most unstable nutrient in the soil and is affected by several reactions such as volatilization, leaching, denitrification and immobilization.…”
Section: Introductionmentioning
confidence: 99%
“…A higher application rate of organo-mineral fertiliser could have resulted in the availability of more nutrients for the growth and development of maize cultivars. Sangoi et al, (2001) posited that increased availability of nitrogen to maize plants would aid their photosynthetic capacity. Improved availability of nitrogen could also have been implicated in the early flowering observed at increased application rate of organo-mineral fertiliser.…”
Section: Discussionmentioning
confidence: 99%